Fig. 1–7 in A new species of Lathrobium Gravenhorst, 1802 (Coleoptera: Staphylinidae, Paederinae) from Kamchatka Peninsula - Ryabukhin, A. S. (Zenodo, 2015)
Fig. 1–7. Lathrobium (Lathrobium) palanum sp. n. 1, 2 – aedeagus: 1 – lateral view; 2 – ventral view; 3-8 – details of structure of abdominal segments without pubescence: 3 – male 8th sternite; 4 – female genital segment, dorsal view; 5 – the same, ventral view; 6 – female 8th tergite; 7 – female 8th sternite. Published as part of Ryabukhin, A. S., 2015, A new species of Lathrobium Gravenhorst, 1802 (Coleoptera: Staphylinidae, Paederinae) from Kamchatka Peninsula, pp. 8-11 in Far Eastern Entomologist 295 on page 9, DOI: 10.5281/zenodo.10084234